Pengaruh Independensi, Keahlian, Frekuensi Rapat, dan Jumlah Anggota Komite Audit terhadap Penerbitan Sustainability Report ISRA 2008-2012 - Ilyona, Risty (Business Accounting Review, 2015)
Consideration of environment issue impact has caused particular concern for the company stakeholders. The company began disclose a report containing the corporate responsibility activities undertaken by more attention to the global framework that is easy to understand and measure the called sustainability reporting, known as CSR report. The reporting guidelines are organized and developed within the Global Reporting Initiative (GRI). These guidelines have been adopted by many companies, including in Indonesia. The purpose of this research is to know the influence of variable independence, expertise, frequency of meetings and the number of audit committees on the disclosure of sustainability report. the size of company is a control variable in this research. The population of this study is all companies registered in ISRA 2013 and the sample is determined by purposive sampling method. The analytical method used is logistic regression analysis. The results of the analysis found that only the frequency of meetings and the size of the companies that affect the sustainability report disclosure.